Effects of radical oxygen species and no: formation of intracellular hypoxia and activation of matrix metalloproteinases in tumor tissues - Burlaka, A.P.; Sidorik, E.P.; Ganusevich, І.І.; Osinsky, S.P. (Experimental Oncology, 2006)
Aim: To establish the association between the radical oxygen species (ROS) and NO levels in the tumor cells mitochondria, between cell hypoxia development and activation of matrix metalloproteinases–2 and -9. Materials and Methods: Electron paramagnetic resonance (EPR) at room temperature and at the temperature of liquid nitrogen (77° K), spin traps technology, enzymography in polyacrylamide gel were applied. Results: Redox-centers in the respiration cascade of mitochondria have been revealed, multiple oxidative damage of which in breast and liver cancer tissues of experimental animals as well as in tumor tissue from patients with gastric cancer promote the development of cell hypoxia. Involvement of ROS and NO in activation of latent forms of matrix metalloproteinases in gastric tumor tissues has been shown. Conclusion: We hypothesize that superoxide radical-anions participate in development of cell hypoxia in tumors and surrounding normal tissues inducing activation of latent forms of matrix metalloproteinases. Цель: установить взаимосвязь между уровнями образования радикальных форм кислорода и оксида азота в митохондриях клеток опухолевых тканей, развитием клеточной гипоксии и активностью матриксных металлопротеиназ – 2 и –9. Методы: электронный парамагнитный резонанс при комнатной температуре и температуре жидкого азота (77 °К), технология Spin Traps, зимография в полиакриламидном геле. Результаты: выявлены редокс-центры в дыхательной цепи митохондрий, множественные окислительные повреждения, которые при канцерогенезе в молочных железах, печени экспериментальных животных и в опухолевой ткани больных раком желудка способствуют развитию клеточной гипоксии; показано участие супероксидных радикал-анионов и оксида азота в активации латентных форм матриксных металлопротеиназ в ткани рака желудка. Выводы: высказано предположение, что в формировании клеточной гипоксии в опухоли и прилегающих нормальных тканях принимают участие супероксидные радикал-анионы, которые активируют при этом латентные формы матриксных металлопротеиназ.